Human tendon stem/progenitor cell-derived extracellular vesicle production promoted by dynamic culture - Clerici, Marta; Ciardulli, Maria Camilla; Lamparelli, Erwin Pavel; Lovecchio, Joseph; Giordano, Emanuele; Dale, Tina P.; Forsyth, Nicholas R.; Maffulli, Nicola; Della Porta, Giovanna (Artificial cells, nanomedicine, and biotechnology, 2025)
Tendon injuries significantly impact quality of life, prompting the exploration of innovative solutions beyond conventional surgery. Extracellular Vesicles (EVs) have emerged as a promising strategy to enhance tendon regeneration. In this study, human Tendon Stem/Progenitor Cells (TSPCs) were isolated from surgical biopsies and cultured in a Growth-Differentiation Factor-5-supplemented medium to promote tenogenic differentiation under static and dynamic conditions using a custom-made perfusion bioreactor. Once at 80% confluence, cells were transitioned to a serum-free medium for conditioned media collection. Ultracentrifugation revealed the presence of vesicles with a 10 particles/mL concentration and sub-200nm diameter size. Dynamic culture yielded a 3-fold increase in EV protein content compared to static culture, as confirmed by Western-blot analysis. Differences in surface marker expression were also shown by flow cytometric analysis. Data suggest that we efficiently developed a protocol for extracting EVs from human TSPCs, particularly under dynamic conditions. This approach enhances EV protein content, offering potential therapeutic benefits for tendon regeneration. However, further research is needed to fully understand the role of EVs in tendon regeneration.